ANALISIS KEBERLANJUTAN PENGENDALIAN PENCEMARAN AIR LIMBAH DOMESTIK GREYWATER MENGGUNAKAN TEKNOLOGI LAHAN BASAH BUATAN - Iga Maliga; Chay Asdak; Efan Yudha Winata (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2021)
Along with the significant increase of population in Bandung City at the moment, domestic wastewater management process must be considered to avoid river contamination, which one of the causes is domestic wastewater disposal without any prior management process. This study is located in Bandung City, which the research was performed in Research Center for Water Resources Office (PUSAIR) Bandung by involving residents of RW 09 Kelurahan Dago as respondents. The method used in this research is a combination of qualitative and quantitative methods. This study aims to analyze the sustainability of the domestic wastewater management process which is carried out using constructed wetlands by considering the economic, environmental, social, and technological aspects. The result shows that the sustainability value of the domestic wastewater management process conducted in the PUSAIR office is approximately 65.2% with the status of moderate sustainability. The detail result of each aspects is economic dimension 62.5%; ecological dimension 75%; social dimension 33.3%; and technological dimension 90%.Keywords: Domestic wastewater, Constructed wetlands, Surface flow techniques, Sustainability analysis